Application of Replicate Organism Detection and Counting Method (RODAC) in Measuring Mycobacterium Tuberculosis Contamination in High Burden Laboratories - Lidya Chaidir; Neng Rina Susilawati; Mandala Ajie; Jessi Annisa; Muti'ah Nurul Jihadah (Althea Medical Journal, 2022)
Background: Technicians working in high burden tuberculosis (TB) laboratories pose a higher risk of being infected by Mycobacterium tuberculosis from clinical samples. Contamination control is mandatory to detect the release of bacteria into the working environment and to minimize the risk of exposure to the workers. The contamination measurement is rarely performed due to the lack of standard methodology. This study optimized and applied a unique culture-based method named Replicate Organism Detection and Counting (RODAC) plates to assess the presence of M. tuberculosis contaminant in the laboratory with high burden of clinical samples. Methods: RODAC was applied on twenty working surfaces in the Mycobacteriology Laboratory of Universitas Padjadjaran. The results of RODAC were compared with DNA-based detection from the same working surfaces using in-house IS6110 real-time PCR (IS6110-qPCR). The detection limit of the RODAC plate was 19.6 CFU mL-1.Results: From all working surfaces tested, two distinct colonies were found on RODAC plate stamped on the Ziehl-Neelsen staining basin. Those colonies were identified as M. tuberculosis and non-tuberculous mycobacteria (NTM), as confirmed by the MPT64 antigen test and the presence of acid-fast bacilli. IS6110-qPCR detected the presence of M. tuberculosis DNA in ten sampling points, including the ZN staining basin, incubators, and microscopy areas. IS6110-qPCR detected more working surface contamination versus RODAC. However, it was noted that RODAC, which was a culture-based method, detected live bacteria, while PCR could not distinguish between live and dead bacteria.Conclusion: The application of the RODAC plate is more suitable for monitoring the contamination of live bacteria in the working environment and to inform a proper corrective action.